Identification, measurement and interpretation of tree rings in woody species from mediterranean climates. (Biological reviews of the Cambridge Philosophical Society, 2003)
We review the literature dealing with mediterranean climate, vegetation, phenology and ecophysiology relevant to the understanding of tree-ring formation in mediterranean regions. Tree rings have been used extensively in temperate regions to reconstruct responses of forests to past environmental changes. In mediterranean regions, studies of tree rings are scarce, despite their potential for understanding and predicting the effects of global change on important ecological processes such as desertification. In mediterranean regions, due to the great spatio-temporal variability of mediterranean environmental conditions, tree rings are sometimes not formed. Often, clear seasonality is lacking, and vegetation activity is not always associated with regular dormancy periods. We present examples of tree-ring morphology of five species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Q. ilex, Q. pubescens) sampled in Tuscany, Italy, focusing on the difficulties we encountered during the dating. We present an interpretation of anomalies found in the wood structure and, more generally, of cambial activity in such environments. Furthermore, we propose a classification of tree-ring formation in mediterranean environments. Mediterranean tree rings can be dated and used for dendrochronological purposes, but great care should be taken in selecting sampling sites, species and sample trees.

Comparative stem-growth rates of Mediterranean trees under background and naturally enhanced ambient CO2 concentrations (New Phytologist, 2000)
Ring widths of five Mediterranean forest tree species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Quercus ilex and Quercus pubescens) growing close to a natural source of CO2 in Tuscany, Italy and at a nearby control site were compared. At the CO2-enriched site, trees have been growing for decades under elevated CO2 concentrations. They originated from parent trees that also grew under elevated CO2 in natural conditions, and they have been continuously exposed to elevated CO2 throughout their growth. Tree-ring series from each of the species were prepared. Assigning calendar dates to rings was difficult but possible, and ring-width series were built for all species. The ring-width data were analysed using a two-sided t-test to assess if there was a difference between the radial growth at the CO2-enriched site and the control site. The cumulative basal area at the same cambial age at both sites was also compared using a Wilcoxon test. Radial growth of trees at the CO2-enriched site was not significantly different from growth at the control site. For each species, year by year, radial growth at the CO2-enriched site was tested against the control site and significant differences were found in only a few years; these differences were not synchronous with extreme climatic events. The expected increase in above-ground productivity, as one of the ecosystem responses to increasing CO2 during drought stress, was not observed in this Mediterranean woody plant community, despite being water-limited. Other resource limitations, such as low nutrient availability (common in the Mediterranean region), may have counteracted the positive effect of elevated CO2 under drought stress, or trees may have acclimated to the high CO2.